A study on correlation between neuroimaging and maternal outcome in eclampsia - Mythreyi Kadambi; Sushma V Dev (Asian Journal of Medical Sciences, 2024)
Background: Hypertensive disorders remain among the most significant complications of pregnancy. Neurological complications of eclampsia are a major contributor to morbidity and mortality that is associated with eclampsia. Neuroimaging studies have revolutionized visualization of hypertensive encephalopathy aids in timely intervention and a favorable maternal and perinatal outcome.